Optimizing scanning in youth female football: The role of verbal instructions - Hintermann, M.; Romann, M.; Lüdin, D.; Taube, W.; Fuchslocher, J. (European Journal of Sport Science, 2025)
Visual exploration, or scanning, is a key perceptual skill in football, enabling players to collect environmental information. It was shown that elite players scan more frequently than less experienced players and make better decisions in subsequent actions. However, to date, it is not clear how to improve and develop scanning behavior. This study examines the immediate effects of verbal instructions on scanning behavior and performance in 4v4 small-sided games among 25 elite youth female football players (mean ± SD age: 17.6 ± 0.7 years). Participants completed two training sessions: one with and one without verbal instructions. Verbal cues were specifically designed to encourage players to scan for teammates, opponents, and free spaces before receiving the ball. Scanning behavior and performance were analyzed using video footage, and data were statistically evaluated through multilevel generalized linear models. Verbal instructions increased the number of scans before ball reception by 27% (rate ratio: 1.27 and 95% CI [1.12, 1.44]), demonstrating their effectiveness in enhancing scanning behavior. Players who performed at least one scan were significantly more likely to achieve successful subsequent actions compared to those who did not scan (e.g., 1 scan: odds ratio = 3.40 and 95% CI [2.59, 4.62]). Notably, the additional scans did not negatively impact the relationship between scanning and the success of subsequent actions. The findings suggest that verbal instructions are a promising coaching tool for increasing the number of scans. Integrating scanning-focused instructions with broader tactical and decision-making training could further optimize perceptual skill development in elite youth football players.